2008
DOI: 10.1080/0972060x.2008.10643680
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oil ofBupleurum exaltatumM.B. Growing Wild in Iran

Abstract: The chemical composition of the volatile oil from aerial parts of Bupleurum exaltatum M.B. has been studied by GC-MS for first time. Forty-nine components (97.3 % of the total composition) were identified. (E)-β-farnesene (29.8 %), germacrene-D (13.3 %), spathulenol (12.9 %), bicyclogermacrene (4.1 %), caryophyllene oxide (3.9 %), myrcene (3.5 %) and α-humulene (3.1 %) were found to be the major constituents of the oil. The oil of B. exaltatum was characterized by a high content of sesquiterpenes (82.2 %), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Moreover, significant variability has been documented for the EOs of H. triquertifolium, which, when collected in Greece, yielded either high amounts of α-pinene together with β-caryophyllene [22] or high percentages of β-caryophyllene and very low quantities of α-pinene [31]. Much diversity has been reported for this plant when collected from different populations in Tunisia [45], while the oils from Iran and Turkey were abundant in germacrene-D and hexanal, respectively [29,50]. Tahir et al [25] characterized the EO from H. triquetrifolium cultures produced by the root and stem for the first time and cited that alkane, aldehyde, and monoterpene compounds are the foremost fractions.…”
Section: Chemical Constituents Of Hypericum Spp Eosmentioning
confidence: 99%
“…Moreover, significant variability has been documented for the EOs of H. triquertifolium, which, when collected in Greece, yielded either high amounts of α-pinene together with β-caryophyllene [22] or high percentages of β-caryophyllene and very low quantities of α-pinene [31]. Much diversity has been reported for this plant when collected from different populations in Tunisia [45], while the oils from Iran and Turkey were abundant in germacrene-D and hexanal, respectively [29,50]. Tahir et al [25] characterized the EO from H. triquetrifolium cultures produced by the root and stem for the first time and cited that alkane, aldehyde, and monoterpene compounds are the foremost fractions.…”
Section: Chemical Constituents Of Hypericum Spp Eosmentioning
confidence: 99%
“…spathulatum Rabson [ 6 ]; germacrene-D (21.7%), β-caryophyllene (18.3%), and δ-cadinene (6.4%) for H. triquetrifolium Turra. [ 7 ] were identified as their major compounds. Similar studies reported also that α-pinene (31.9 ± 1.9%), (E)-β-ocimene (12.5 ± 1.0%), β-phellandrene (8.4 ± 1.1%), and β-pinene (6.3 ± 0.4%) for H. helianthemoides (Spech) Boiss [ 8 ]; α-pinene (19.0%), germacrene D (12.5%), and β-pinene (8.7%) for H. empetrifolium Willd [ 9 ]; β-selinene (15%), caryophyllene oxide (9%), β-caryophyllene (8%), and γ -muurolene (7%) for H. pruinatum Boiss [ 10 ]; α-pinene (57.3%), β-pinene (9.0%), and limonene (6.2%) for H. hyssopifolium Chaix.…”
Section: Introductionmentioning
confidence: 99%